Comparison of characteristics of Q beta replicase-amplified assay with competitive PCR assay for Chlamydia trachomatis. - An, Q (1995)
In order to study infections due to Chlamydia trachomatis, we have compared semiquantitative PCR and Q beta replicase-amplified assays for detection of this organism. The PCR assay was directed against the C. trachomatis 16S rRNA gene. Quantitation was accomplished by adding known amounts of a plasmid containing a truncated segment of the 16S rRNA gene target to chlamydia-containing samples and then amplifying with a common primer set. The Q beta replicase assay consisted of reversible target capture of C. trachomatis 16S rRNA, which was followed by amplification of an RNA detector probe in the presence of the enzyme Q beta replicase. In a clinical matrix, the lower limit of detection of both the PCR and Q beta replicase assays was five elementary bodies. The Q beta replicase and PCR assays were quantitative over 10,000- and 1,000-fold ranges of organisms, respectively. Analysis of the effects of endocervical matrix on amplification was accomplished by examining 94 endocervical specimens by each technique. Both assays detected five of six culture-confirmed specimens as well as three culture-negative specimens. PCR inhibitors were detected in 13 specimens. The Q beta replicase assay, in contrast, showed no evidence of sample inhibition. The Q beta replicase and PCR assays should allow quantitative investigation of infections due to C. trachomatis. In addition, because it targets highly labile RNA, the Q beta replicase assay may facilitate investigations into the role of active persisting infection in culture-negative inflammatory conditions.